Contemporary Belarusian Dialects in Lithuania (Vilnius Region) - Jankowiak, Mirosław (Slavistica Vilnensis, 2021)
The aim of the article is to present contemporary Belarusian dialects in south-eastern Lithuania (in the Vilnius region), which have been the subject of linguistic research but not comprehensive. The basis of the analysis is mainly the author’s own materials, materials taped by other dialectologists and dictionary entitled Слоўнік беларускіх гаворак паўночна-заходняй Беларусі і яе пагранічча. The structure of these Belarusian dialects (selected features in phonetics, morphology, syntax, vocabulary and phraseology) as well as the sociolinguistic aspect of their use in a multilingual environment are demonstrated in this article.The analysis of the collected material shows that the structure of Belarusian dialects in the study area is well-preserved. Belarusian dialectologists regard the Belarusian dialect in Vilnius Region as a south-western dialect, which should be described in detail. In the statement of interlocutors, one can note the phonetic, morphological and syntactic features typical for: the south-western dialect, the Central Belarusian subdialects, the Grodno-Baranavichy group of the south-western dialect and the two so-called dialectal zones: western and north-western. Local Belarusian dialects have been influenced by Baltic and Polish for hundreds of years and we can notice numerous borrowings from these and their dialects.
Keywords: dialectology; Belarusian dialects in Lithuania; Slavic-Baltic language borderland; language contacts; borrowings